A Novel Approach to Topological Indices of the Power Graph Associated with the Dihedral Group of a Certain Order - Abdul Gazir Syarifudin; Laila Maya Santi; Nurina Fadlila Shaumi; Erma Suwastika; I Gede Adhitya Wisnu Wardhana (University of Mataram, 2025)
Power graph of a group G, represented by Γ_G, is a graph where the vertex set consists of the elements of G. Two distinct vertices a, b G are connected by an edge if and only if there exists a positive integer m such that a^m = b or b^m = a. This study explores the utilization of a new approach to compute the topological indices of power graph associated with dihedral group with n=p^k, p is primes and k Z. Results obtained indicate that the topological indices calculated using new approach yield the same values as those obtained with the conventional approach.